Double diffraction radiation target interferometry for micro-train beam diagnostics; 5th International Particle Accelerator Conference IPAC’14, 15 – 20 June, 2014, Dresden, Germany - Shkitov D. A. Dmitriy Andreevich; Potylitsyn A. P. Alexander Petrovich; Aryshev A. S. Aleksandr Sergeevich; Urakawa J. (Instrumentation, Controls, Feedback & Operational Aspects, 2014)
Title screen